Outcomes of laparoscopic sleeve gastrectomy in elderly obese Japanese patients. Issue 11 (30th March 2017) - Hayashi, Aiko; Maeda, Yukari; Takemoto, Minoru; Tokuyama, Hirotake; Koide, Hisashi; Kitahara, Aya; Hayashi, Hideki; Kitamoto, Takumi; Yamaga, Masaya; Kobayashi, Kazuki; Yokote, Koutaro
Abstract: Aim: Laparoscopic sleeve gastrectomy (LSG) has proven to be the most effective strategy for the treatment of morbid obesity, however its efficacy and safety in an aging population has not yet been confirmed. In this study, we evaluated the effectiveness and safety of LSG in elderly obese Japanese patients. Methods: Three obese individuals aged >60 years and 11 obese individuals aged <60 years who underwent LSG were enrolled. Pre‐ and postoperative changes after at least 12 months were examined, including bodyweight, body mass index, total weight loss, excess weight loss, bone mineral density and bone‐related markers. Results: There were no significant differences between patients aged <60 years and >60 years in terms of percent total weight loss (24.4 ± 11 vs 23 ± 4.4%, respectively) and percent excess weight loss (49.1 ± 23.4 vs 47.6 ± 10 %, respectively). Dual‐energy X‐ray absorptiometry was carried out before and 12 months after LSG. There were no significant differences in bone mineral density changes at the lumbar spine and femoral neck between the two groups (0.01 ± 0.06 vs 0.02 ± 0.03 g/cm 2, −0.03 ± 0.06 vs −0.08 ± 0.02 g/cm 2, respectively). There were no peri‐ and postoperative complications. All three patients aged >60 years had reduced bone mineral density in the femoral neck after LSG; one was diagnosed with osteoporosis. Conclusions: Although the present results suggest that LSG could be of considerable benefit to elderly obese Japanese patients, long‐term careful observation after bariatric surgery is especially important in elderly patients to prevent future osteoporosis.Geriatr Gerontol Int 2017; 17: 2068–2073 .